Histopathological lesions in spontaneous dictyocaulotic pneumonia of the reindeer (Rangifer tarandus tarandus L.) - Rahko, Timo; Saari, Seppo; Nikander, Sven (Rangifer, 1992)
The histopathology of pneumonitic lesions in natural lungworm infection has not been previously described in reindeer. In the present study, light microscopical studies of dictyocaulotic lung tissues were performed on 12 slaughtered reindeer specimens obtained from the eastern part of Finnish Lapland in order to reveal the histopathological lesions characteristic of spontaneous Dictyocaulus eckerti infection. The lungs of 8 healthy reindeer carrying no lung worms were investigated to elucidate normal microscopic structure. Parasites in different stages of development and their eggs were detected not only in inflamed sections of small airways, but also wandered freely in the alveolar lumina. The eggs were rich in carbohydrates for reserve energy and were surrounded by a superficial layer of acidic mucins. The pleural serosa over acutely inflamed areas was swollen and in chronically altered sections, fibrotic thickenings of pleural and subpleural tissues were evident. The lung tissues were either condensed by an inflammatory exudate rich in migrating cells or emphysematically altered. Mucus secretions were abnormally profuse and apparently less acidic in histochemical compositon. Interstitial tissues were also inflamed and contained separated foreign body and eosinophilic granulomes. Furthermore, a vasculitis with endothelial vacuolations and muscular hypertrophy was noticeable in some tissue sections.